(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This is driven by the increased use of engineered nanoparticles and the increased pressure to commercialize this growing technology. Over the last few decades there was significant interest in nanotechnology research utilizing nanoparticles like metals , semiconductors metal oxides, which are of great interest to a wide range of applications in the fields of knowledge, electricity, environmental medical technology due to their special or improved properties, primarily defined by scale, composition structure Present research focuses on the production, forms, characterization and most modern nanotechnology applications